(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the possibilities and advantages of adaptive platforms in language learning in the modern educational process. It also discusses the world experience in the implementation of artificial intelligence in education, as well as the future development directions and expected results of this technology. The integration of artificial intelligence into the educational process serves to improve the quality of modern pedagogy and the learning process. As a result of research and analysis, artificial intelligence technologies in the educational system require the creation of intelligent educational systems that adapt to the individual needs of students. In order to meet this requirement, the development of an adaptive learning system based on artificial intelligence technologies requires a step-by-step approach. During the research, we developed a stable model for future digital educational platforms based on advanced artificial intelligence technologies, aimed at creating a person-centered, safe, flexible and effective learning environment. Through this model, individual tasks are recommended based on the level of knowledge of students, which further increases the effectiveness of the intended result. A methodology has been developed for developing flexible algorithms that optimize the learning process in adaptive learning environments based on the student’s individual behavior, knowledge status, and level of mastery.